Pelaksanaan Jaminan Pembiayaan Mudharabah di Bank Syariah - Isnaini Isnaini (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
This study discusses the issues of securities financing of mudharabah in sharia banking. In response to this investigation, the study used qualitative normative jurisprudence methods by analyzing primary and secondary data to generate answers to existing problems. The result of this study is that the application of mudharabah financing securities in Shariah banks still apply the guarantee to mudharib. A mudharabah transaction is a form of cooperation between two or more parties in which the owner of the capital (shahibul maal) entrusts a certain amount of capital to the management (mudharib) with a profit sharing agreement. This form underscores cooperation with the one hundred percent contribution from shahibul maal and entrepreneurs from mudharib. Mudharabah is an agreement entered into between the two contracting parties. In Indonesia, the practice of using guarantees for mudharabah financing was enacted by Law No. 10 of 1998 on banking and Law No. 21 of 2008 on sharia banking and Fatwa of the Shariah Council of the National Council of Indonesian Scholars (DSN-MUI) Number: 07 / DSN-MUI / IV / 2000 which also allows for a guarantee.